Penerapan Pembelajaran Kontekstual Untuk Mengembangkan Kemampuan Siswa SMP Negeri 18 Kota Bengkulu - Yumarni, Asmara; Isnaini, Rohmatul; Sari, Anggel Permata; Junita, Selly; Nurfadilah, Bety (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to explore the application of contextual learning in improving students’ abilities in junior high school. Contextual learning is expected to link the subject matter with students’ daily lives, so that they can understand the concepts more deeply and relevantly. Through this approach, students are expected to not only acquire knowledge, but also develop critical thinking skills, creativity, and social abilities that are essential for facing challenges in the modern world. This research used a qualitative method with a case study design, which involved interviews, observations, and document analysis to collect data from students and teachers. The results of the study are expected to provide insights into effective strategies in the implementation of contextualized learning, as well as the challenges faced in the process. Thus, this study aims to provide recommendations for educators and educational institutions in implementing contextual learning more effectively, in order to improve the quality of education and the development of students’ abilities.